Z tygodnia na tydzień, z powieści na powieść, z meczu na mecz jako przykłady nieswobodnych grup syntaktycznych - Gębka-Wolak, Małgorzata; Moroz, Andrzej (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The article has verified a hypothesis suggesting that the sequences mentioned in the title and similar to them are constrained syntactic groups, i.e., they do not form a regular combination of simple signs. The verification has been conducted on the basis of a three-stage procedure taking into account the semantic features and inner qualities of the studied expressions, namely, their composition as well as the structural and linear links between segments. It has been indicated that the components of the studied sequences jointly express meaning which can be considered as a form of perlocution: ‘something changes within fragments of time undergoing observation whose measure is determined by a variable component’. Moreover, it has been demonstrated that the two components of a sequence that can be exchanged can be realized not only by standard measures of time (second, minute, hour, week), but also by nouns referring to events (match, meeting, term). Also, there is a presentation of the basic limitations in the realization of a variable component and a mutual linear arrangement of variable and constant components. A characteristic of the expressions of the type from week to week, from novel to novel, from match to match is supplemented by the remarks concerning their external syntax.